Charge-Enhanced Hydrogen Bond and Brønsted Acid Catalysis: An Evolving Frontier - Vemulapalli, Srini; White, Brandon; Kovljenic, Nenad; Dudding, Travis (Synthesis, 2025)
In catalysis, both rate acceleration and selectivity are of central importance, and strategies to achieve these outcomes remain fundamental to advancing synthetic methodology. Over the past two decades, the merger of traditional catalytic paradigms with charge-enhancing elements has led to unprecedented reactivity in bond-forming processes with broad synthetic utility. These systems augmented by charge are increasingly attracting attention for their unique modes of activation. In particular, this review highlights and contextualizes recent advancements in charge-enhanced hydrogen bond and Brønsted acid catalysis that enable novel activation modes complementary to traditional catalytic platforms. Special emphasis is placed on catalysts such as amidinium, cyclopropenium, and azolium ions as well as cationic thiourea and phosphoric acids, whose charge-enhanced features have enabled transformative improvements in reactivity, rate acceleration, and selectivity.
Keywords: Hydrogen-bonding; Brønsted acidity; Stereoselectivity; Rate-enhancement; Cyclopropenium; Phosphoric acid; Thiourea; Amidinium